Tailoring of optical and mechanical properties of high-entropy ceramic thin flms prepared by hipims sputtering; Перспективы развития фундаментальных наук; Т. 1 : Физика - Bulakh V. A. Vlada Aleksandrovna (2023, 2023)
Заглавие с экрана